Dietary intake of nutrients involved in one‐carbon metabolism and risk of urothelial cell carcinoma: A prospective cohort study. Issue 2 (1st March 2018) - Dugué, Pierre‐Antoine; Brinkman, Maree T.; Hodge, Allison M.; Bassett, Julie K.; Bolton, Damien; Longano, Anthony; Hopper, John L.; Southey, Melissa C.; English, Dallas R.; Milne, Roger L.; Giles, Graham G.
Abstract : Nutrients involved in one‐carbon metabolism may play a role in carcinogenesis through DNA replication, repair and methylation mechanisms. Most studies on urothelial cell carcinoma (UCC) have focused on folate. We sought to examine the association between B‐group vitamins and methionine intake and UCC risk, overall and by subtype, and to test whether these associations are different for population subgroups whose nutritional status may be compromised. We followed participants in the Melbourne Collaborative Cohort Study ( N  = 41, 513) for over 20 years and observed 500 UCC cases (89% originating in the bladder; superficial: 279, invasive: 221). Energy‐adjusted dietary intakes of B vitamins (B1, B2, B3, B5, B6, B8, B9 and B12) and methionine were estimated from a 121‐item food frequency questionnaire administered at baseline (1990–1994), using the residuals method. We used Cox regression models to compute hazard ratios (HRs) of UCC risk per standard deviation (SD) of log‐transformed nutrient intakes and 95% confidence intervals, adjusted for potential confounders. We investigated associations by tumor subtype, and tested interactions with sex, country of birth, smoking and alcohol drinking. The risk of UCC appeared not to be associated with intake of B‐group vitamins or methionine, and findings were consistent across tumor subtypes and across demographic and lifestyle characteristics of the participants. A potential interaction between vitamin B1 and alcohol drinking was observed (all participants: HR per 1 SD = 0.99 (0.91–1.09), never drinkers: HR = 0.81 (0.69–0.97), p ‐interaction = 0.02), which needs to be confirmed by other studies. Our findings do not indicate that dietary intake of nutrients involved in one‐carbon metabolism are associated with UCC risk. Abstract : What's new? Changes in DNA methylation are associated with an increased risk of urothelial‐cell carcinoma (UCC). Because B vitamins and methionine play key roles in DNA synthesis, methylation and repair, they might also influence carcinogenesis. In this prospective study, however, the authors found no evidence that intake of these nutrients affects a patient's risk of developing UCC, either positively or negatively. They also found no association with tumor aggressiveness nor with risk in the presence of other risk factors such as smoking or alcohol use.